Impact of anticoagulation and antiplatelet drugs on surgery rates and mortality in trauma patients - Felix M. Bläsius (Nature Portfolio, 2021)
Abstract Preinjury anticoagulation therapy (AT) is associated with a higher risk for major bleeding. We aimed to evaluated the influence of preinjury anticoagulant medication on the clinical course after moderate and severe trauma. Patients in the TraumaRegister DGU ≥ 55 years who received AT were matched with patients not receiving AT. Pairs were grouped according to the drug used: Antiplatelet drugs (APD), vitamin K antagonists (VKA) and direct oral anticoagulants (DOAC). The primary end points were early (< 24 h) and total in-hospital mortality. Secondary endpoints included emergency surgical procedure rates and surgery rates. The APD group matched 1759 pairs, the VKA group 677 pairs, and the DOAC group 437 pairs. Surgery rates were statistically significant higher in the AT groups compared to controls (APD group: 51.8% vs. 47.8%, p = 0.015; VKA group: 52.4% vs. 44.8%, p = 0.005; DOAC group: 52.6% vs. 41.0%, p = 0.001). Patients on VKA had higher total in-hospital mortality (23.9% vs. 19.5%, p = 0.026), whereas APD patients showed a significantly higher early mortality compared to controls (5.3% vs. 3.5%, p = 0.011). Standard operating procedures should be developed to avoid lethal under-triage. Further studies should focus on detailed information about complications, secondary surgical procedures and preventable risk factors in relation to mortality.